EXERTIONAL HEAT STROKE DALAM AKTIVITAS OLAHRAGA: EVALUASI FAKTOR PENYEBAB, PENATALAKSANAAN, DAN UPAYA PENCEGAHAN: SUATU TINJAUAN PUSTAKA - Yudha Hariyadi; Neiyfa Naura; Andi Kurniawan; Nuryani Sidarta; Erica Kholinne (Fakultas Kedokteran Universitas Trisakti, 2026)
Heat illness has become an increasing public health concern in the context of global climate change, which has led to a progressive rise in environmental temperatures. One of the most severe forms of heat illness is exertional heat stroke (EHS). EHS is a medical emergency characterized by a core body temperature exceeding 40°C accompanied by central nervous system dysfunction, including altered mental status. This condition commonly occurs in individuals performing high-intensity physical activity, particularly in environments with elevated temperature and humidity. This paper aims to discuss the etiological factors, preventive strategies, and management of EHS. Environmental factors, especially temperature and humidity, play a crucial role in both the development and prevention of EHS. The management of EHS emphasizes rapid and continuous body cooling as the primary intervention, along with airway stabilization, limitation of endogenous heat production, optimization of circulation, and close monitoring and treatment of complications. Rapid reduction of core body temperature remains the most critical determinant in reducing morbidity and mortality. This paper is expected to enhance understanding of early recognition, management, and prevention of exertional heat stroke.